Profil Sektor Informal di Kabupaten Ponorogo - Asis Riat Winanto; Khusnatul Zulva Wafirotin (Al Tijarah, 2016)
The informal sector in Ponorogo is an everyday phenomenon that is controversial. But the issue of the informal sector can not be left alone, because the day of their number grew in number and will result in teranggunya public space. To that end, the necessary data and information about the characteristics of the informal sector, as historically their efforts, the motivation to enter this sector, where they came from, educational background and experience, and so forth. This study aimed to determine the profile of the informal sector in Ponorogo. Results from this study indicate that it appears that the age group that most respondents are in the age group of 20-4; type of informal businesses followed, the majority of angkringan selling coffee, the majority of marital status is married with the level of education is dominated by high school graduates. Being the majority of them coming from the area of origin Ponorogo; with a daily average profit of Rp300.000,00. Medium initial capital used an average of Rp1.000.000,00-Rp3.000.000,00; with long pkerjaan who lived for more than 10 years.